Effects of differential irrigation and nitrogen reduction replacement on winter wheat yield and water productivity and nitrogen-use efficiency - Shen, Hongzheng; Gao, Yunhe; Sun, Kexin; Gu, Yuhui; Ma, Xiaoyi (Agricultural water management, 2023)
Rational irrigation and chemical nitrogen fertilizer increase crop yield, water productivity (WP), and nitrogen-use efficiency (NUE), but excessive amounts of water and nitrogen increase nitrogen loss and negatively affect the soil and environment. Controlled-release fertilizers and organic fertilizers can replace chemical fertilizers, but their mechanisms for crop growth, yield, and water and nitrogen use are still unclear. This study conducted a 2-year field experiment to quantify the effect of irrigation and nitrogen reduction replacement on winter wheat growth, yield, WP, and NUE. The results indicated that irrigation water of 90 mm per time decreased the WP and increased soil water storage and evapotranspiration (ET). Compared with the no-nitrogen treatment, irrigation and nitrogen reduction replacement increased the leaf area index and chlorophyll content by 26.5–47.0% and 17.7–31.5%, respectively. In addition, the average yield of winter wheat 2 years after treatment with 75% of the traditional nitrogen rate (75% U), the traditional nitrogen rate (U), polymer-coated urea (PCU), and urea combined with organic fertilizer (U+OM) increased by 68.2%, 85.1%, 81.9%, and 95.1%, respectively, and the average nitrogen uptake of grains increased by 90.0%, 117.5%, 111.9%, and 147.2%, respectively. Compared with the nitrate nitrogen after U treatment, the residual nitrate nitrogen in a 0–160-cm soil profile after 75% U, PCU, and U+OM treatments decreased by 42.0%, 25.4%, and 9.7%, respectively. The average NUE of winter wheat increased by 4.7–30.5% after 2 years. The yield of winter wheat was significantly correlated with physiological growth indices (except for ET and 1000-grain weight), WP, and NUE. Large amounts of irrigation water did not significantly increase winter wheat yield, WP, or NUE. Therefore, when the irrigation volume is 60 mm, winter wheat can be sustainably produced with high WP and NUE values by using PCU treatment or a combination of urea and organic fertilizer. The results of this study can also provide reference and basis for winter wheat production in similar eco-climate areas. •More irrigation reduced water productivity (WP) and increased evapotranspiration.•Nitrogen reduction replacement improved winter wheat growth and grain nitrogen uptake.•Polymer-coated urea significantly improved the WP and nitrogen-use efficiency.•Urea combined with organic fertilizer increased grain yield significantly.